KONSEKUENSI SIFAT FINAL DAN MENGIKAT PUTUSAN MAHKAMAH KONSTITUSI TERHADAP PUTUSAN YANG BERPOTENSI KELIRU - Dedi Mulyadi; Ardelia Lananda; Feyza Ashila Putri Hidayat; Suci Muldiyanti; Syifa Apriliani (LPPM Universitas Doktor Husni Ingratubun Papua, 2026)
Constitutional Court decisions have the unique characteristic of being final and binding. This characteristic means that decisions made by the Constitutional Court immediately acquire permanent legal force upon pronouncement and are binding on all citizens, state institutions, and related parties. The absence of further legal remedies such as appeals, cassation, or judicial review makes Constitutional Court decisions absolute in the Indonesian constitutional system. On the one hand, this characteristic aims to guarantee legal certainty, maintain the stability of the legal system, and prevent conflicts of interpretation of the constitution. However, on the other hand, this final and binding nature can raise problems if the resulting decision has the potential to contain errors in the interpretation of norms, legal considerations, or resulting policy implications. This condition creates a dilemma between the principles of legal certainty and substantive justice in constitutional practice. This study aims to analyze the consequences of the final and binding nature of Constitutional Court decisions on the possibility of potentially erroneous decisions. The method used is a normative approach by examining relevant laws and regulations, legal theory, and doctrine. The results of the study show that although a final and binding nature is necessary to maintain the supremacy of the constitution, an academic oversight mechanism and constitutional evaluation are still needed to minimize the potential for errors in Constitutional Court decisions.